2009
DOI: 10.1021/nn900368b
|View full text |Cite
|
Sign up to set email alerts
|

Increased Heating Efficiency and Selective Thermal Ablation of Malignant Tissue with DNA-Encased Multiwalled Carbon Nanotubes

Abstract: Nanoparticles, including multiwalled carbon nanotubes (MWNTs), strongly absorb near-infrared (nIR) radiation and efficiently convert absorbed energy to released heat which can be used for localized hyperthermia applications. We demonstrate for the first time that DNA-encasement increases heat emission following nIR irradiation of MWNTs, and DNA-encased MWNTs can be used to safely eradicate a tumor mass in vivo. Upon irradiation of DNA-encased MWNTs, heat is generated with a linear dependence on irradiation tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
179
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(183 citation statements)
references
References 24 publications
2
179
1
1
Order By: Relevance
“…This lateral opening of the chain, resulting in an encapsulation anisotropy of ∆ϕ max =16.5º, is clearly a reversible process because d(Ψ 12 , Ψ 13 ) falls back to the purely crystalline B-DNA values during the observed time window. The two symmetrical shoulders located at regions defined by nucleotide indices (20)(21)(22) and (8)(9)(10), evidencing a slight distance decrease between contacts, need to be carefully analysed. is performed for the maximum number of allowed H-bonds for a particular donor-acceptor pair.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This lateral opening of the chain, resulting in an encapsulation anisotropy of ∆ϕ max =16.5º, is clearly a reversible process because d(Ψ 12 , Ψ 13 ) falls back to the purely crystalline B-DNA values during the observed time window. The two symmetrical shoulders located at regions defined by nucleotide indices (20)(21)(22) and (8)(9)(10), evidencing a slight distance decrease between contacts, need to be carefully analysed. is performed for the maximum number of allowed H-bonds for a particular donor-acceptor pair.…”
Section: Resultsmentioning
confidence: 99%
“…Because the DNA had been artificially inserted, no information about the encapsulation process itself, e.g., its thermodynamical spontaneity and kinetics, was provided. Previous experiments and calculations indicate that the biomolecule can be confined onto D = 2.7 nm SWCNTs 13 and D = 3-4 nm multi-walled carbon nanotubes (MWCNTs) 20,21 , however, the corresponding working temperatures (350 -400K) were far too high to have any physiological relevance. Furthermore, the experimental observations of Iijima et al indicated that encapsulation of DNA onto MWCNTs was a competing mechanism with wrapping of the biomolecule around the external wall 20 ; their reported data failed to identify the relevant conditions upon which the confinement process is favoured, such as ionic strength of the media and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is direct injection of antibody bound nanoparticles at the tumor site with a high degree of specificity with minimum effect on healthy tissues [50,51]. The in vivo therapeutic utility of nanoparticles is growing based on energy utilization from different sources of magnetic fields, microwaves, lasers and ultrasound to the tumor tissue [52][53][54].…”
Section: Techniques Of Tumor Targeting and Therapymentioning
confidence: 99%
“…Most of the studies involving SWNTs or other nanoparticles-assisted photothermal treatment were based on high laser power density of 1-40 W/cm 2 [23][24][25][26][27][28]. However, high laser power density could cause non-selective photothermal damage to the surrounding normal tissues.…”
Section: Introductionmentioning
confidence: 99%